2016
DOI: 10.1002/lary.26444
|View full text |Cite
|
Sign up to set email alerts
|

Thiol/disulfide homeostasis as a novel indicator of oxidative stress in obstructive sleep apnea patients

Abstract: 3b. Laryngoscope, 127:E244-E250, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…They can be reduced and oxidised by dynamic thiol/disulphide homeostasis in the case of oxidative stress. There is an increasing body of evidence for the presence of abnormal thiol/disulphide homeostasis in the pathogenesis of diseases such as diabetes mellitus [14], cardiovascular diseases [10,11], cancer [15], rheumatoid arthritis [16], chronic kidney disease [17], obstructive sleep apnoea [18], and Parkinson's disease [19]. In the present study, we also demonstrated that oxidative stress levels are higher in patients with NSTE-ACS using dynamic thiol/disulphide parameters.…”
Section: Discussionsupporting
confidence: 69%
“…They can be reduced and oxidised by dynamic thiol/disulphide homeostasis in the case of oxidative stress. There is an increasing body of evidence for the presence of abnormal thiol/disulphide homeostasis in the pathogenesis of diseases such as diabetes mellitus [14], cardiovascular diseases [10,11], cancer [15], rheumatoid arthritis [16], chronic kidney disease [17], obstructive sleep apnoea [18], and Parkinson's disease [19]. In the present study, we also demonstrated that oxidative stress levels are higher in patients with NSTE-ACS using dynamic thiol/disulphide parameters.…”
Section: Discussionsupporting
confidence: 69%
“…Beyond schizophrenia, other putative metabolite-phenotype associations from this analysis appeared to be feasible as well: cysteinylglycine disulfide (associated with sleep duration) is a disulfide, and disulfides have been explored as a marker of stress in obstructive sleep apnea 64 , and glutaroylcarnitine (associated with cognitive performance) levels are known to be altered in glutaric acidemia type 1, which can manifest in neurological problems like dystonia 65 . Among the novel findings, N-delta-acetylornithine (associated with schizophrenia) was also associated with cognition and alcoholism.…”
Section: Discussionmentioning
confidence: 99%
“…Authors have demonstrated that NT levels were significantly lower in patients with benign paroxysmal positional vertigo, seasonal allergic rhinitis, Bell's palsy, obstructive sleep apne and nasal polyposis [53][54][55][56][57].…”
Section: Head and Neck Pathologiesmentioning
confidence: 99%